Microemulsion of methanol extract of Tridax procumbens flower and its antibacterial activity against Streptococcus mutans and Enterococcus faecalis - Wijayanti, Sri; Pradana, Agrin Febrian; Situmeang, Boima; Prastiwi, Dina Alva; Musa, Weny J.A. (Universitas Nusa Cendana, 2025)
Tridax procumbens (commonly known as Gletang flower) is a medicinal plant recognized for its antibacterial potential and is widely distributed across various habitats such as rice fields, plantations, and roadsides. Phytochemical screening of its methanolic flower extract revealed the presence of secondary metabolites, including alkaloids, flavonoids, steroids, phenols, terpenoids, and tannins, all of which contribute to its biological activities. This study aimed to develop a microemulsion formulation of T. procumbens methanolic extract and to evaluate its antibacterial activity against Streptococcus mutans and Enterococcus faecalis, two major oral pathogenic bacteria. The microemulsion was prepared using the sonication method and characterized by assessing its pH, transmittance, viscosity, physical stability, and particle size using a particle size analyzer. Antibacterial activity was tested using the Kirby-Bauer disk diffusion method. The results indicated that the microemulsion had particle sizes ranging from 300–1000 nm and demonstrated significantly higher antibacterial activity compared to the crude extract, suggesting improved solubility and enhanced bioactivity of the active compounds. This formulation holds promise as a natural antibacterial agent for the prevention of oral infections.